Temperament Characteristics and Strategy Inventory for Language Learning: Mediating Students Speaking Online Learning - Asri Nurlaely; John Pahamzah (Journal of English Language Teaching and Cultural Studies, 2022)
In teaching and learning process of English, the teacher should manage both students temperament and language learning strategies since those have contribution to the students’ language achievements along with the purposes of the education. The objectives of this research are (1) to investigate is there any correlation between students’ temperament characteristics with speaking skill; (2) to investigate is there any correlation between the strategy inventory for language learning with students’ speaking skill; and (3) to investigate is there any correlation between students’ temperament characteristics and the strategy inventory for language learning with students’ speaking skill. This research was employed by quantitative approach through correlation method. The population was the students at Holmesglen Language Centre Tangerang, and the researcher took 30 students as the sample. This research proves that the sig.F change value is 0.532 > 0.05, so the decision was Ho was accepted and Ha was rejected. This concludes that there is no significant correlation between temperament characteristics, strategy inventory for language learning with speaking skill.